Analysis of confirm factor analysis in Competency of Thai Local Journalists - Wantippa, Darun (NIDA Development Journal, 2018)
The objective of this study was to analyze the competence of Thai local newspaper journalists with Confirmatory Factory Analysis and Quantitative Research Methodology. Data collection had been operated with the questionnaire created from literature review, which was applied to evaluate the competence of Thai local newspaper journalists in every organization for 350 persons. The result would be processed and concluded. The competence of Thai local newspaper journalists consists of 12 dimensions which are 1) experiences 2) news writing skill 3) website/multimedia skill 4) work under pressure and time-limited 5) be sportsmanly 6) communication skill 7) news evaluation 8) leadership 9) accuracy10) software/computer skill 11) creativity 12) resource development. According to the validation of a goodness of fitted model yielded a Chi-square of ( / df) = 0.944 (less than 2), P = 0.876 (more than 0.05), RMSEA = 0.000 (less than 0.05), GFI = 0.911 (more than 0.90), and AGFI = 0.888 (more than 0.85). Considering Factor Loading, all passed the criteria (more than 0.6) and the appropriateness of observable factors of the overall model according to the validity test; it was found that AVE is over 0.45 in every latent variable while CR of latent variables is over 0.6 as well. In consequence, the newspaper journalists must develop their competence all the time in order to create quality news including searching for more new resources, learning the international language; these skills and technology can be applicable to their works. Most importantly, the newspaper journalists must have a good attitude towards their news. In other words, they must hold on morality and mainly concern on mutual benefits. Next, they have to build motivation to the readers in analyzing news issues. Additionally, each must have their own writing style, for example.